Sexual behaviour and poor hygiene are related to recent hepatitis a virus community outbreaks - Hernández Bustabad, Alberto; Morales Arráez, Dalia; González, Alejandra; de Vera, Antonia; Díaz-Flores, Felicitas; Lecuona Fernández, María; Gómez-Sirvent, Juan Luís; Avellón Calvo, Ana; Hernández-Guerra, Manuel (Revista española de enfermedades digestivas, 2020)
there has been a global increase in the incidence of hepatitis A infection. The aim of this study was to examine the characteristics of the increase in our region and the degree of adherence to the recommended hygienic measures after discharge from hospital. demographic, clinical and biochemical variables were collected from patients with acute hepatitis A in our health area. The patients were grouped as follows: January 2010 to December 2016 (historical cohort) and January 2017 to October 2017 (recent cohort). A phylogenetic analysis was also performed in the recent cohort. One month after discharge, bacterial growth was evaluated by a culture of the dominant hand imprint and were compared with a control group. a total of 110 cases were registered with a median age of 36.3 years (range 3-89) and 77.3 % were male. The incidence was 0.82/100,000 inhabitants/year and 22.75/100,000 inhabitants/year in the historical and recent cohorts, respectively. Patients in the recent cohort were more frequently male (52.6 % vs. 82.4 %, p = 0.008) and younger (51.7 [3-89] vs. 33.4 [4-74] years, p < 0.001). In addition, 63.8 % of the recent cohort were men who had sex with other men and had unsafe sexual practices (37.5 %). Phylogenetic analysis showed a predominance of genotype A and a high frequency of the VRD 521-2016 sequence. A higher growth of enterobacteria was observed in patients with hepatitis A compared to the control group (7.3 % vs. 1.2 %, p = 0.005), despite specific hygienic measures given at discharge. a recent outbreak of hepatitis A in our area was related with gender, younger age and sexual practices. Hepatitis A infected subjects showed a poor adherence to hygienic measures. Our data suggests the need for policies that encourage preventive actions, particularly vaccination in this high-risk group.